2011
DOI: 10.1159/000332847
|View full text |Cite
|
Sign up to set email alerts
|

Acne Management in Japan: Study of Patient Adherence

Abstract: Obtaining good adherence to acne therapy is a challenge for all dermatologists. We studied 428 acne patients in Japan to determine the likelihood of good adherence and factors associated with medication-taking. This study utilized a simple validated questionnaire to assess risk of poor adherence; information about patient and treatment characteristics was also collected. There was an overall rate of poor adherence in 76% of subjects. Adherence to topical medication was poor in 52% of those treated with a topic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
4
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 29 publications
2
27
4
3
Order By: Relevance
“…The small number of patients lost to follow-up suggests a high adherence to this long-term maintenance protocol among our study patients. Nevertheless, adherence to daily treatment was not objectively assessed [40]. …”
Section: Discussionmentioning
confidence: 99%
“…The small number of patients lost to follow-up suggests a high adherence to this long-term maintenance protocol among our study patients. Nevertheless, adherence to daily treatment was not objectively assessed [40]. …”
Section: Discussionmentioning
confidence: 99%
“…In turn, improved understanding may lead to greater treatment adherence and clinical outcomes. 19,20 …”
Section: Discussionmentioning
confidence: 99%
“…Clinical experience and recent published data suggest that adherence is the main critical aspect for the therapy's success [16]; non-adherence to treatment, in fact, is a well-known challenge associated with poor health outcomes and increased utilization of healthcare resources. Miyachi et al [4] reported that in Japanese acne patients there was an overall rate of poor adherence in 76% of subjects; adherence to topical medication was poor in 52% of patients treated with only one topical product, and among those taking combination therapies, adherence to the topical portion of therapy was poor in 49% of subjects.…”
Section: Discussionmentioning
confidence: 99%
“…As acne is a chronic condition and its treatment lasts several years, the patient's adherence to the therapeutic program represents a key point [3]. Several studies, in fact, suggest that adherence to acne medications is often poor; factors with an impact on adherence included satisfaction with treatment and the experience of side effects [4]. There is no unique validated score to measure adherence worldwide and some strategies can be very helpful to implement it.…”
Section: Introductionmentioning
confidence: 99%